2020
DOI: 10.1002/ehf2.12667
|View full text |Cite
|
Sign up to set email alerts
|

Desmin‐related myopathy characterized by non‐compaction cardiomyopathy, cardiac conduction defect, and coronary artery dissection

Abstract: Desmin-related myopathy (DRM) is a rare heritable cardiac and skeletal muscle disease caused by mutations in the desmin gene (DES). DRM is generally characterized by skeletal muscle weakness, conduction disturbance, and dilated cardiomyopathy. However, the clinical cardiac phenotypes of DRM are not yet fully understood. Herein, we report the first case of DRM with the de novo missense DES mutation, R454W, that is characterized by left ventricular non-compaction cardiomyopathy, progressive cardiac conduction de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Kulikova et al reported in this Special Issue an LVNC family carrying the DES missense mutation p.A337P, leading to a severe filament assembly defect in transfected cells [ 35 ]. This genetic finding is in good agreement with further reports of other groups identifying DES as a novel LVNC gene [ 36 , 37 , 38 ]. In contrast to monogenic inherited cardiomyopathies, AF is a complex heart rhythm disorder caused by environmental and multi-genic risk factors [ 39 ] and significantly increases the risk for stroke and heart failure.…”
supporting
confidence: 93%
“…Kulikova et al reported in this Special Issue an LVNC family carrying the DES missense mutation p.A337P, leading to a severe filament assembly defect in transfected cells [ 35 ]. This genetic finding is in good agreement with further reports of other groups identifying DES as a novel LVNC gene [ 36 , 37 , 38 ]. In contrast to monogenic inherited cardiomyopathies, AF is a complex heart rhythm disorder caused by environmental and multi-genic risk factors [ 39 ] and significantly increases the risk for stroke and heart failure.…”
supporting
confidence: 93%
“…Respiratory muscle weakness is a major complication in patients with DRM, sometimes leading to respiratory failure and death (Tamiya et al, 2020).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“… 2 Non‐compaction cardiomyopathy has also been reported in patients with cardiac disease. 12 Arrhythmic manifestations include atrioventricular conduction defects, bundle branch blocks, atrial fibrillation, and ventricular tachycardia. 8 …”
Section: Discussionmentioning
confidence: 99%